2013
DOI: 10.1051/epjpv/2013023
|View full text |Cite
|
Sign up to set email alerts
|

Passivation effects of atomic-layer-deposited aluminum oxide

Abstract: Atomic-layer-deposited (ALD) aluminum oxide (Al2O3) has recently demonstrated an excellent surface passivation for both n-and p-type c-Si solar cells thanks to the presence of high negative fixed charges (Q f ∼ 10 12 −10 13 cm −2 ) in combination with a low density of interface states (Dit). This paper investigates the passivation quality of thin (15 nm) Al2O3 films deposited by two different techniques: plasmaenhanced atomic layer deposition (PE-ALD) and Thermal atomic layer deposition (T -ALD). Other dielect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 33 publications
2
56
0
Order By: Relevance
“…These results reveal that the field-effect passivation due to negative fixed charges is activated only for post-deposition annealed Al 2 O 3 films, and that the extracted negative fixed charge density Q f is within a range similar to that observed on silicon surfaces. [9][10][11][12] This indicates that the field-effect passivation quality achieved by the PDA films on CIGS surfaces is comparable to that achieved by ALD Al 2 O 3 films on silicon surfaces. [9][10][11] Furthermore, due to the presence of highly negative Q f values in the PDA films, the net concentration of minority carriers (n s ) at the CIGS surface will be reduced, thereby satisfying one of the requirements to reduce the surface recombination rate (U s ) according to the Shockley-Read-Hall formalism.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…These results reveal that the field-effect passivation due to negative fixed charges is activated only for post-deposition annealed Al 2 O 3 films, and that the extracted negative fixed charge density Q f is within a range similar to that observed on silicon surfaces. [9][10][11][12] This indicates that the field-effect passivation quality achieved by the PDA films on CIGS surfaces is comparable to that achieved by ALD Al 2 O 3 films on silicon surfaces. [9][10][11] Furthermore, due to the presence of highly negative Q f values in the PDA films, the net concentration of minority carriers (n s ) at the CIGS surface will be reduced, thereby satisfying one of the requirements to reduce the surface recombination rate (U s ) according to the Shockley-Read-Hall formalism.…”
mentioning
confidence: 73%
“…The concept of passivating CIGS surfaces using ALD Al 2 O 3 films is based on previous experience gained from silicon solar cell technologies. [9][10][11][12] The surface passivation of silicon substrates using ALD Al 2 O 3 films has drawn intense attention from the silicon photovoltaic community because of these films' ability to passivate p-and n-type as well as highly doped p + silicon surfaces effectively. 9,10 This passivation ability is attributed to a high density of negative Q f (10 12 -10 13 cm −2 ) in the Al 2 O 3 bulk (field-effect passivation) in combination with a low interface-trap charge density D it (10 10 -10 12 eV −1 cm −2 ) at the Al 2 O 3 /Silicon interface (chemical passivation).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in several publications that ALD of Al 2 O 3 , when not deposited correctly, can result in a significant amount of trapped negative charge, resulting in a p-doping effect on the affected transistor. 13,14 When the top-gate metal was added, it balanced the intrinsic charge in the Al 2 O 3 and allowed the G-FET to act as if the charge had been removed.…”
Section: Resultsmentioning
confidence: 99%
“…Kotipallia et al [12] showed the D it reduction at the silicon/dielectric interface by using hydrogen gas annealing to reduce the dangling bonds. Schultz et al [13] showed the influence of thermal oxidation temperature on the D it of the interface.…”
Section: Introductionmentioning
confidence: 99%